Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.5194/acpd-10-19469-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tropical deep convection and its impact on composition in global and mesoscale models - Part 1: Meteorology and comparison with observations.

Abstract: Tropical convection is a very important atmospheric process acting on the water cycle, radiative budget of the atmosphere and air composition of the upper troposphere and lower stratosphere (UTLS), and it affects a broad range of spatial and temporal scales. The fast vertical transport in convective plumes can efficiently redistribute water vapour and pollutants up to the Tropical Tropopause Layer (TTL), and therefore affect the composition of the lower stratosphere. Chemistry Climate Models and Chemistry Tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In the first paper (Russo, 2010) (hereafter R 2010), we present a comparison of the models' meteorological parameters with satellite-based measurements. In this second paper we compare the results of model tracer transport.…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper (Russo, 2010) (hereafter R 2010), we present a comparison of the models' meteorological parameters with satellite-based measurements. In this second paper we compare the results of model tracer transport.…”
Section: Introductionmentioning
confidence: 99%
“…Even though convection is parameterised in the model, recent studies find that this very model setup is suitable for transporting VSLS as shown by comparing the distribution of modelled high cloud to observations (Russo et al, 2010) and vertical transport of idealised short-lived tracers (Hoyle et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies provide further evidence that this very model setup is suitable for transporting VSLS as shown by comparing the distribution of modelled high cloud to observations (Russo et al, 2010) and vertical convective transport of idealised short-lived tracers (Hoyle et al, 2010). This analysis allows for the comparison between competing hypotheses for troposphere-stratosphere transport (TST), namely of Newell and Gould-Stewart (1981) who proposed a "Stratospheric Fountain" where the Maritime Continent and West Pacific are the main region for TST, and Liu and Zipser (2005) who argue for many "Stratospheric Fountains" (driven by convection over Africa, Maritime Continent and South America).…”
Section: Introductionmentioning
confidence: 90%